2015
DOI: 10.2139/ssrn.2707498
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Macroprudential Policies in Developing Asia: An Empirical Analysis

Abstract: The global financial crisis highlighted the need for national bank supervisory authorities to improve surveillance systems and to detect early on the buildup of macroeconomic risks that could threaten the entire financial system. This paper presents an empirical framework for analyzing how effective macroprudential policies control credit growth, leverage growth, and housing price appreciation. Two significant findings emerge. Broadly, macroprudential policies can indeed promote financial stability in Asia. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Lee et al (2015) found that credit-related policies significantly decrease credit expansion and housing price rise, whereas liquidity-related policies effectively reduce leverage and rapid increase in housing price. Lee et al (2015) found that credit-related policies significantly decrease credit expansion and housing price rise, whereas liquidity-related policies effectively reduce leverage and rapid increase in housing price.…”
Section: Macroprudential Policiesmentioning
confidence: 99%
“…Lee et al (2015) found that credit-related policies significantly decrease credit expansion and housing price rise, whereas liquidity-related policies effectively reduce leverage and rapid increase in housing price. Lee et al (2015) found that credit-related policies significantly decrease credit expansion and housing price rise, whereas liquidity-related policies effectively reduce leverage and rapid increase in housing price.…”
Section: Macroprudential Policiesmentioning
confidence: 99%
“…He concludes that a macroprudential policy shock is effective in curbing excessive credit growth and house price appreciation. Lee, Asuncion, and Kim (2015) apply the Qual VAR to investigate how effectively macroprudential policies mitigate financial stability risks in Asia. They suggest that credit-related macroprudential policy tools can be more effective in dampening credit expansion than liquidity-related macroprudential policy instruments.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…These included: (i) strengthening financial supervision and macroprudential regulations to address NPLs and restore banking sector confidence, (ii) adopting measures to stem short-term capital outflows and raising interest rates to reduce investor flight, (iii) establishing more flexible exchange rate regimes, and (iv) instituting a broader set of reforms to restructure the banking sector and develop and deepen capital markets. Lee, Asuncion, and Kim (2015); Lee, Gaspar, and Villaruel (2017); Lee (2016);and Villafuerte (2017).…”
Section: Conclusion and Policy Considerationsmentioning
confidence: 99%